The Impact Of Credit Risk On The Profitability Of Commercial Banks: A Cross Country Analysis (UK, US & Nigeria) - Musa, Malliya Bello (2013)
Credit risk has traditionally been one of the greatest risks faced by banks. The recent global credit crisis has re-emphasized its major impact on the wellbeing and profitability of businesses (Brown and Moles, 2012). This study reviews the existing literature on the theoretical concepts and empirical evidence on best practice credit risk management (CRM) tools and techniques employed by banks. Using annual bank data from 2006 to 2011, the impact of credit risk on the profitability of commercial banks in developed and developing countries is examined. A quantitative research approach is employed using financial ratio analysis (FRA) and a panel data regression model driven by credit risk indicators. The FRA suggests Nigerian banks have higher credit risk but with a decreasing trend from 2006 to 2009, before deteriorating in 2009. In contrast, deteriorating asset quality was documented for the developed countries from 2006, with improvements for the US from 2010.